Photonic nanojets in coupled microcavities - Donegan, John; Mc Closkey, David (IEEE, 2009)
Dielectric transparent microspheres are three-dimensional spherical microcavities which provide high Q-factors and a small mode volume leading to strong optical feedback within the cavity. This paper investigates the optical properties of symmetrically arranged micrcavities (photonic molecules) with regards to resonance modes and directional beam emission by means of photonic nanojets. The unique feature of nanojets is a directional beam with a beam waist smaller than the diffraction limit. In contrast to diffraction-limited microlensing, the nano-jet phenomenon is a near-field effect due to the proximity of the focus position and the microsphere surface. Also because of the nano-scale beam waist, the photonic nano-jets can reach a very high intensity. This offers new opportunities for a broad range of applications in biophotonics, plasmonics, optical data storage and ultramicroscopy. One of the motivations for this research is to examine the feasibility of subdiffractional resolution of imaging and sub-wavelength optical signal waveguiding. Using finite-element computational approach,it is found that a plane-wave-illuminated lossless dielectric microsphere generates a photonic nanojet propagating for a distance of approximately one micrometer in the attached microsphere. Strongly directed far field emission in 3-sphere, 5-sphere and 7-sphere structures are expirementally observed. The directional emission from the photonic molecules matches the symmetry of the structure with 3 jets located at 120 degrees with respect to each other for the triangular photonic molecule.
European Conference on Lasers and Electro-Optics 2009 and the European Quantum Electronics Conference (CLEO Europe - EQEC 2009)
PUBLISHED
Munich
Keywords: Physics